O espaço ficcional e o efeito do horror nas narrativas fantásticas de Álvares de Azevedo - Santos, Carline Barbon dos (2016)
This research aims to analyze the construction of an important narrative element - the space, the construction of the horror of climate and hesitation present in fantastic narratives of Macário and Noite na Taverna ultraromantic writer Alvares de Azevedo. For the basis of reflections on the fantastic and horror effect, this work the theoretical ground the writings of Tzvetan Todorov, HP Lovecraft, Noël Carroll, Remo Ceserani and on theories that will base the approach on space, we will use the Michel Foucault and Osman Lins. In addition, the development of research is fundamental points verifying the constituent aspects of fantasy literature in Alvares de Azevedo, the analysis of how the fictional spaces collaborate to the horror effect and hesitation on the reader, and also an understanding of how spaces psychologically design the characters in the two works cited. We hope that, after a thorough analysis of interesting author's work Alvares de Azevedo, we can come to a conclusion, relating both narratives with the notion of building space in the narrative, and especially with the reader's hesitation front of the stranger, noting that the feeling of "strangeness" is quite likely to come across the fantastic.